2021
DOI: 10.2196/27075
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatments for Legg-Calvé-Perthes Disease: Comprehensive Review

Abstract: Background Legg-Calvé-Perthes disease (LCPD) is a common public health problem that usually occurs between the ages of 4 and 8 years, but it can occur between the ages of 2 and 15 years. This condition occurs due to the interruption of blood supply to the femoral head. Up to now, different surgical and nonsurgical treatments, including femoral varus osteotomy, innominate osteotomy, pelvic osteotomies, triple osteotomy, Chiari osteotomy, and shelf acetabuloplasty, have been suggested for noncontaina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 99 publications
(134 reference statements)
0
11
0
Order By: Relevance
“…In patients 6 to 8 years of age, the prognosis is variable and depends on the severity of the disease. Patients under 6 years of age have an excellent prognosis comparable to conservative treatment [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients 6 to 8 years of age, the prognosis is variable and depends on the severity of the disease. Patients under 6 years of age have an excellent prognosis comparable to conservative treatment [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of Salter’s innominate osteotomy and femoral varus osteotomy is used when only one of these procedures is insufficient to cover the femoral head within the acetabulum. The principal indications for using these techniques are late clinical onset, severe femoral head involvement, evidence of lateral subluxation, lateral calcification, or considerable changes in the metaphysis [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of quantitative data, bilaterality of ONFH it was not possible to investigate separately. Finally, articles concern-Life 2022, 12, 179 9 of 12 ing Perthes disease have been excluded, as the management of these patients has been extensively analysed in the literature [70][71][72][73][74][75][76][77][78][79][80][81][82], and evidence on non-Perthes related ONFH is limited. Two studies which have been included for analysis reported data on patients with Perthes disease [31,33]; however, since the authors reported the results separately, data from patients with Perthes disease were not considered.…”
Section: Discussionmentioning
confidence: 99%
“…Presentation of Perthes disease has been reported in certain patients with increased susceptibility (Maleki et al, 2021;Miyamoto et al, 2017). Genetic mutation of COL2A1 has been reported to be involved in the genesis of a type II collagenopathy and a possible cause of LCPD (Kannu et al, 2011;Li et al, 2014).…”
Section: Discussionmentioning
confidence: 99%